Financial Exposure Carl Levin's Senate Investigations into Finance and Tax Abuse - Bean, Elise J. (Springer International Publishing, 2018)
At a time when Congressional investigations have taken on added importance and urgency in American politics, this book offers readers a rare, insider's portrait of the world of US Congressional oversight. It examines specific oversight investigations into multiple financial and offshore tax scandals over fifteen years, from 1999 to 2014, when Senator Levin served in a leadership role on the US Senate Permanent Subcommittee on Investigations (PSI), the Senate's premier investigative body. Despite mounting levels of partisanship, dysfunction, and cynicism swirling through Congress during those years, this book describes how Congressional oversight investigations can be a powerful tool for uncovering facts, building bipartisan consensus, and fostering change, offering detailed case histories as proof. Grounded in fact, and written as only an insider could tell it, this book will be of interest to financial and tax practitioners, policymakers, academics, students, and the general public.